2009
DOI: 10.1007/s10735-009-9252-z
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Cajal-like cells of human Fallopian tube express estrogen and progesterone receptors

Abstract: Cells of the female reproductive tract are subject to hormonal control via sex steroid genomic receptors expressed at nuclear level. We previously showed that interstitial Cajal-like cells (ICLC) of human myometrium expressed estrogen and progesterone receptors (ER/PR). Our aim, based on these results, was to see if ER and/or PR could be found also in tubal ICLC. Indeed, we present here immunohistochemical evidence that ICLC of human Fallopian tube (isthmic region) have such receptors. Stromal ICLC, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 50 publications
(54 reference statements)
5
65
0
3
Order By: Relevance
“…It has also been stated that the contractility of smooth muscle cells in the female genital tract is regulated by sex steroids [12]. Results of in vitro studies have demonstrated a strong nuclear co-localisation of estrogen (ER) and progesterone receptor (PR) in CD 117-positive cells of the human female genital tract [13,14]. These results suggest that myometrial CD 117-positive cells could behave as sensors, controlling myometrial contractility, depending on steroid hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been stated that the contractility of smooth muscle cells in the female genital tract is regulated by sex steroids [12]. Results of in vitro studies have demonstrated a strong nuclear co-localisation of estrogen (ER) and progesterone receptor (PR) in CD 117-positive cells of the human female genital tract [13,14]. These results suggest that myometrial CD 117-positive cells could behave as sensors, controlling myometrial contractility, depending on steroid hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…TCs are considered to be signal modulators and transducers because of their organization into networks and their close affinity with nerve endings, capillaries, and other cell types [Yang et al, 2012]. Therefore, it can be suggested that TCs in seminal vesicles could act as steroid sensors, possibly via a gap junction-mediated mechanism [Cretoiu et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 and PGF 2α increase muscle contraction, whereas PGE 1 decreases muscle contraction (Wanggren et al 2008). Evidence indicates that the contraction is possibly regulated by both E 2 and P 4 , as estrogen and progesterone receptors (ESR and PGR) are expressed in the interstitial Cajallike cells in the muscle cell layer of the oviduct (Cretoiu et al 2009). The function of the muscle contraction is generally recognized to be for sperm transport purposes (Overstreet & Cooper 1978a).…”
Section: Smooth Muscle Contractionmentioning
confidence: 99%